2021
DOI: 10.1002/jctb.6681
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments on magnetic molecular imprinted polymers (MMIPs) for sensing, capturing, and monitoring pharmaceutical and agricultural pollutants

Abstract: Among the many classes of pollutants, bioactive contaminants including pesticides, herbicides, and other pharmaceutical active compounds (PhACs) are causing significant concern. These chemicals have been linked directly to contamination of freshwater and food sources, threatening water and food security. Contamination from antibiotics, one class of PhACs, is also considered to link strongly to the global problem of antimicrobial resistance (AMR). Pollution from these contaminants has hit developing countries h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Different levels of DEX and other glucocorticoid pollutants exist in hospital wastewater, city sewage and river water in the range of 52–390 ng L −1 , 7,8 and could have a serious impact on biological and human health through the food chain and bioaccumulation 8,9 . Several studies have reported that conventional wastewater treatment plants based primarily on biological processes are not effective in removing such pharmaceuticals; 10 in this view, their technological upgrade incorporating advanced oxidation processes may be essential to achieve higher removal efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Different levels of DEX and other glucocorticoid pollutants exist in hospital wastewater, city sewage and river water in the range of 52–390 ng L −1 , 7,8 and could have a serious impact on biological and human health through the food chain and bioaccumulation 8,9 . Several studies have reported that conventional wastewater treatment plants based primarily on biological processes are not effective in removing such pharmaceuticals; 10 in this view, their technological upgrade incorporating advanced oxidation processes may be essential to achieve higher removal efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Having magnetic properties under certain controlled conditions of process operations can imply that these spent magnetic multiple-template adsorbent-type molecularly imprinted polymers can be recovered from the treated effluent streams quasi entirely by applying an appropriately designed external magnetic field. In this way, the application of the centrifugation and filtration unit operations for the separation and recovery of micropollutant-loaded adsorbent-type molecularly imprinted polymers can be avoided (Aylaz et al 2021 ). Fourth, green and environmentally compatible disposal routes have to be designed for regenerating as much as possible the completely exhausted multiple-template adsorbent-type molecularly imprinted polymers.…”
Section: Limitations Of Molecularly Imprinted Polymersmentioning
confidence: 99%
“…After isolating the polymer, the template is removed [ 1 ]. This results in specific binding sites that allow for the specific binding that differentiates imprinted polymers from non-imprinted resins [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Common Syntheses For Imprinting Polymerizationsmentioning
confidence: 99%
“…At this point, MIPs are used in many different applications. Broadly, they can be grouped into two categories: Detection and sensing for a variety of compounds, from contaminants to proteins in cells [6][7][8][9][10][11][12][13][14][15][16][17][18] and extraction and purifications of compounds from environmental and biological samples [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%